PERAN PEMERINTAH KABUPATEN PEKALONGAN DALAM PENYEDIAAN SEKOLAH INKLUSIF PENYANDANG DISABILITAS BERDASARKAN PERATURAN DAERAH NOMOR 2 TAHUN 2020 - R??? ??????? ??????; Dewi Erowati (Journal of Politic and Government Studies, 2026)
This study aims to analyze the role of the Pekalongan Regency Government in providing inclusive education for persons with disabilities, particularly students who are deaf and those with speech impairments, and to identify the obstacles encountered in its implementation in 2023. This research is motivated by the importance of ensuring equal and non-discriminatory access to education as mandated by existing laws and regulations. This study employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving the Department of Education and Culture, school principals, teachers, and inclusive education stakeholders. The results indicate that the Pekalongan Regency Government has contributed to the provision of inclusive education through the establishment of inclusive schools, provision of supporting facilities, and the implementation of affirmative policies in student admissions. However, several challenges remain, including the limited number of qualified teachers in special education, uneven distribution of disability-friendly facilities, and administrative as well as social constraints. Therefore, strengthening policies, improving teacher competencies, and enhancing collaboration among government, schools, and the community are necessary to achieve effective, equitable, and sustainable inclusive education.